Mi casa sin mí parada no es casa: Conceptualizations of functioning and functional impairment in rural Chiapas, Mexico - Sarah Joy Hartman; Néstor Noyola; Viena Murillo; Fátima Rodríguez Cuevas; Esteban V. Cardemil (Elsevier, 2023)
In mental healthcare, functional impairment is an essential element in diagnosing and monitoring the severity of mental disorders. However, current clinical practices do not account for how context and culture might shape conceptions of functional impairment, given the demonstrated influence of cultural context on mental health, particularly in Mexico. We interviewed 16 members of a rural community in Chiapas, Mexico to understand how they understood functioning and how functioning is impacted by distress. We analyzed the data using thematic analysis with a critical lens. With regards to conceptions of functioning, participants described that to function was to work (nuestra vida es el trabajo), to satisfy the family's needs (poder satisfacer las necesidades de la familia), and to be at ease (estar a gusto). When participants, many of whom had been diagnosed with depressive and/or anxiety disorders, were distressed, they explained that their work (oficio) and family (familia) were impacted. All of the themes were influenced by the importance of family, economic oppression, and gender roles. The results demonstrate that mental healthcare providers must account for cultural context in psychological distress and functional impairment.